2004
DOI: 10.1163/156853904322890780
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial opportunities for polygamy in a monogamous seahorse, Hippocampus whitei

Abstract: The sex with the higher potential reproductive rate is expected to mate polygamously unless there are temporal or spatial constraints on mate availability. We investigated whether such constraints were evident in a population of the monogamous seahorse Hippocampus whitei (family Syngnathidae). Across the whole study site, breeding was more asynchronous than expected by chance. Our findings are thus compatible with the hypothesis that asynchronous breeding may promote and/or maintain monogamy. Asynchrony per se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 37 publications
0
3
1
Order By: Relevance
“…It was found that the population on the Manly net started breeding in late September and continued until the end of February during this 1 year study, but clearly the exact duration of breeding may vary between years. The abundance of seahorses decreased at the conclusion of the breeding season and it is believed they moved off the net into the surrounding seagrass meadows and deeper waters (Vincent, 1995;Vincent et al, 2004). This differs from the findings of Clynick (2008) who found no seasonal variation in seahorse populations on nets at Balmoral and Clifton Gardens.…”
Section: Discussioncontrasting
confidence: 58%
“…It was found that the population on the Manly net started breeding in late September and continued until the end of February during this 1 year study, but clearly the exact duration of breeding may vary between years. The abundance of seahorses decreased at the conclusion of the breeding season and it is believed they moved off the net into the surrounding seagrass meadows and deeper waters (Vincent, 1995;Vincent et al, 2004). This differs from the findings of Clynick (2008) who found no seasonal variation in seahorse populations on nets at Balmoral and Clifton Gardens.…”
Section: Discussioncontrasting
confidence: 58%
“…This is similar to the report that the difference in the reproductive rate of male and female Syngnathus typhle increases as the fish age (Svensson, 1988). However, this does not display that the older seahorses have better quality offspring, and the quality is generally correlated with the brood pouch development, gestation time and parental investment (Vincent et al, 2004; Lin et al, 2008; Naud et al, 2009). …”
Section: Discussionmentioning
confidence: 85%
“…In some syngnathid species, the reproduction is influenced by the complex brooding structure, brood pouch development, sexual selection, mating patterns and social promiscuity (Parker and Simmons, 1996; Carcupino et al, 2002; Wilson et al, 2003; Vincent et al, 2004; Lin et al, 2006; Naud et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…In this fish family, monogamy is widely distributed regardless of the complexity of the brood pouch, phylogenetic relationship and geographical distribution (Wilson et al, 2001(Wilson et al, , 2003. All monogamous syngnathids so far reported are non-territorial, and home ranges of individuals overlap with each other (Matsumoto & Yanagisawa, 2001;Vincent et al, 2004). Therefore, limited availability of mates or resources does not seem to explain the maintenance of their monogamy.…”
Section: Introductionmentioning
confidence: 99%